Quantifying cellular capacity identifies gene expression designs with reduced burden - Ceroni,F; Algar,R; Stan,G-B; Ellis,T (Nature Methods, 2015)
Heterologous gene expression can be a significant burden forcells. Here we describe an in vivo monitor that tracks changesin the capacity of Escherichia coli in real time and can be usedto assay the burden imposed by synthetic constructs and theirparts. We identify construct designs with reduced burden thatpredictably outperformed less efficient designs, despite havingequivalent output.